Improving Access to Delivery Care and Reducing the Equity Gap Through Voucher Program in Bangladesh: Evidence From Difference-in-Differences Analysis. (January 2018) - Keya, Kaji Tamanna; Bellows, Benjamin; Rob, Ubaidur; Warren, Charlotte
To test a statistically significant change in delivery by medically trained providers following introduction of a demand-side financing voucher, a population-based quasi-experimental study was undertaken, with 3, 300 mothers in 2010 and 3, 334 mothers at follow-up in 2012 in government-implemented voucher program and control areas. Results found that voucher program was significantly associated with increased public health facility use (difference-in-differences (DID) 13.9) and significantly increased delivery complication management care (DID 13.2) at facility although a null effect was found in facility-based delivery increase. A subset analysis of the five well-functioning facilities showed that facility deliveries increased DID 5.3 percentage points. Quintile-based analysis of all facilities showed that facility delivery increased more than threefold in lower quintile households comparing to twofold in control sites. The program needs better targeting to the beneficiaries, ensuring available gynecologist–anesthetist pair and midwives, effective monitoring, and timely fund reimbursements to facilities.